Comparison of three commercial enzyme-linked immunosorbent assays for the diagnosis of Classical Swine Fever - Aguilar-Vargas, Fernando; Carvajal, Fabian; Guzmán, Mónica; León, Bernal (Archives of Veterinary Science, 2023)
Classical swine fever (CSF) is a highly contagious viral disease that affects both pigs and wild boars. The disease can cause significant economic losses in the pig industry and poses a threat to food security. Therefore, it is crucial to have effective surveillance programs for detecting and controlling the disease. The aim of this study was to compare three commercial ELISA kits for detecting CSF antibodies. The results showed that all three kits had 100% congruence in undiluted samples, indicating that they are highly reliable for use as a screening test on routine samples. Additionally, the study found good reproducibility between technicians with no significant influence on the variation of results. However, the study also identified a low consistency of positive results (37.7%) for the kit IDvet Screen E2 in diluted samples, with significant variations in results from all three kits. This finding suggests that the other two kits, Herdchek E2 and Priocheck E2, may be better suited for detecting animals with low levels of antibodies, allowing for earlier detection of infected animals and implementation of relevant control measures. In conclusion, the study demonstrates the importance of using high-quality commercial ELISA kits for CSF surveillance. The findings suggest that any of the three kits tested could be used as a reliable screening test on routine samples. However, for detecting animals with low levels of antibodies, the Herdchek E2 and Priocheck E2 kits may be more effective.